Effect of Different Sowing Dates on Yield and Yield component traits of Wheat - Chaulagain, Bhimsen; Bhattarai, Rajendra Kumar; Pokharel, Bhanu Bhakta (Agronomy Journal of Nepal, 2024)
An experiment was conducted in winter season of 2020/21 and 2021/22 to evaluate the effects of different sowing dates on phenological traits, yield attributing traits and grain yield of wheat. The experiment was carried-out in Agronomy farm of National Agronomy Research Center, Khumaltar, Lalitpur, Nepal. The experiment was conducted in randomized complete block design (RCBD) with six sowing dates (10 Nov, 20 Nov, 30 Nov, 10 Dec, 20 Dec and 30 Dec) as treatment which were replicated four times. Wheat variety Swargdwari was used in the experiment. During the experiment, we took different observations starting from phenological parameters to yield traits like days to 50% flowering, days to 90% maturity, plant height, spike length, number of grains per spike, number of tillers per square meter, thousand grain weight, grain yield, straw yield and harvest index. The combined ANOVA of two years revealed that there was significant effect of sowing dates on days to 50% flowering, days to 90% maturity, plant height at physiological maturity, spike length, straw yield and grain yield of wheat. Number of grains per spike found non-significant. Number of tillers per square meter was found maximum (374.1) m-2 on 20 Nov. Thousand grain weight was found maximum on 10 Nov which was 54.37 g followed by 20 Nov with 51.77g. Straw yield was found the highest on 10 Nov which was 9.05 tha-1 followed by 7.83 tha-1 on 20 Nov. Similar result was shown by grain yield with maximum value of 6.13 tha-1 on 10 Nov followed by 20 Nov which is 5.90 tha-1. Harvest index was found maximum on 10 Dec with 0.49. Nov sowing had more vegetative growth contributing higher straw yield and low economic return. Therefore, it is concluded that 10 Nov is optimum time for wheat sowing in Kathmandu valley and similar agro-climatic regions.